2011
DOI: 10.1038/srep00015
|View full text |Cite|
|
Sign up to set email alerts
|

A novel potent tumour promoter aberrantly overexpressed in most human cancers

Abstract: The complexity and heterogeneity of tumours have hindered efforts to identify commonalities among different cancers. Furthermore, because we have limited information on the prevalence and nature of ubiquitous molecular events that occur in neoplasms, it is unfeasible to implement molecular-targeted cancer screening and prevention. Here, we found that the FEAT protein is overexpressed in most human cancers, but weakly expressed in normal tissues including the testis, brain, and liver. Transgenic mice that ectop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 58 publications
1
50
0
Order By: Relevance
“…The most significant TCG is METTL13 (methyltransferase like 13), which was correlated with sum of NFT density estimates in the superior parietal lobule (BM7-SPL) ( r  = 0.70, P value = 1.25 × 10 –8 ). The protein product encoded by this gene is the antiapoptotic protein FEAT, which is also aberrantly overexpressed in various human cancer tissues [37]. Among the list of the top trait correlated genes is AKT2 , which encodes a serine/threonine-protein kinase Akt.…”
Section: Resultsmentioning
confidence: 99%
“…The most significant TCG is METTL13 (methyltransferase like 13), which was correlated with sum of NFT density estimates in the superior parietal lobule (BM7-SPL) ( r  = 0.70, P value = 1.25 × 10 –8 ). The protein product encoded by this gene is the antiapoptotic protein FEAT, which is also aberrantly overexpressed in various human cancer tissues [37]. Among the list of the top trait correlated genes is AKT2 , which encodes a serine/threonine-protein kinase Akt.…”
Section: Resultsmentioning
confidence: 99%
“…In transgenic mice, Mettl13 ectopic overexpression can drive tumorigenesis in vivo (55). Moreover, gene expression profiling of NIH3T3 cells overexpressing METTL13 dysregulated the RTK and hedgehogsignaling pathways (55). Intriguingly, METTL13 is predicted to have methyltransferase activity, spermidine/spermine synthase activity, or ubiquinone synthase activity, but these functions of METLL13 have not been experimentally demonstrated (55).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has low expression in normal tissues including the testis, brain, and liver (55). In transgenic mice, Mettl13 ectopic overexpression can drive tumorigenesis in vivo (55). Moreover, gene expression profiling of NIH3T3 cells overexpressing METTL13 dysregulated the RTK and hedgehogsignaling pathways (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancers develop from the dysregulation of genes involved in normal development and tissue homeostasis (Garraway & Lander, ; Hanahan & Weinberg, ; Vogelstein et al, ). We have previously found that f aint e xpression in normal tissues, a berrant overexpression in t umors (FEAT), the protein encoded by methyltransferase‐like 13 ( METTL13 ), potently drives tumorigenesis in transgenic mice (Takahashi et al, ). FEAT is aberrantly upregulated in most human cancers including colorectal, pancreatic, prostate, breast, ovary, thyroid, and non‐small‐cell lung cancers.…”
Section: Introductionmentioning
confidence: 99%